The Middle Palaeolithic Assemblage with Bahari Technique from the Site 21b in Deir el‑Bahari (Western Thebes), Upper Egypt - Barbara Drobniewicz (Archaeologia Polona, 2020)
In the 1970s, the authors of this paper explored the Site 21b, situated in the north-western fringe of the Deir el-Bahari Valley, in the Theban Massif (Upper Egypt). Based on the significant variability in the state of preservation of artefacts’ surfaces, six series of artefacts were identified, corresponding to the Middle Palaeolithic and Pre-Dynastic assemblages. The most detailed analysis was performed for the inventory of the series 2, which was ascribed to a previously unknown industry with the Levallois technique and Mousterian discoidal cores. This industry is also characterised by an occurrence of a specific manner of obtaining flakes from globular and thick, flattened, lens-like nodules, abundantly occurring in the local Lower Eocene limestone. This manner of flake production was called the Bahari technique. Due to the occurrence of sidescrapers, Mousterian points, denticulated and notched pieces, the chronology of this series was determined as Middle Palaeolithic.